Identification of manganese-responsive microRNAs in Arabidopsis by small RNA sequencing - Jian Gong; Dong Li; Hao Li; Huakun Zhou; Jin Xu (Czech Journal of Genetics and Plant Breeding, 2019)
Manganese (Mn) is an important micronutrient for growth and development in plants, however, excess Mn is harmful by disrupting photosynthesis system and inducing oxidative damage in leaves. MicroRNAs (miRNAs) play key roles in regulating Mn toxicity tolerance in plants. Here, we identified Mn toxicity-responsive miRNAs in Arabidopsis by using small RNA sequencing. Eighteen differentially expressed miRNAs were identified in Arabidopsis thaliana seedlings in response to Mn toxicity. These differentially expressed miRNAs are involved in regulating nutrition homeostasis, transport, stress response, and developmental processes. Our results indicated that these miRNAs play a key role in Mn toxicity response in plants.